The Effect of Packaging and Labeling On Consumer Buying Interest of Sampeu Wedang - Kurniawan, Ryan Feryana; Septiyani, Anisa; Sopia, Astri Dewi Yulianti; Lestari, Astri Indah; Afenti, Erni; Willyan, Imey Meylan (Universitas Sebelas April, Fakultas Ekonomi dan Bisnis, 2025)
This study aims to analyze the effect of packaging and labeling on consumer purchasing interest in Sampeu Wedang products. Packaging and labeling are important elements in a marketing strategy that not only protect the product, but also serve as a visual communication medium to attract consumers' attention. This study uses a quantitative approach with a survey technique. Data were collected through questionnaires distributed to 50 respondents, using a census technique because the population is relatively small. The results of the study indicate that both packaging and labeling have a significant positive effect on consumer purchasing interest. Attractive packaging design, clear information on the label, and suitability with consumer preferences have proven to be the main factors influencing purchasing decisions. This study provides recommendations to Sampeu Wedang producers to improve the quality of packaging and labeling as a strategy to increase product appeal in the market